Karyotypes and Sex Chromosomes in Two Australian Native Freshwater Fishes, Golden Perch (Macquaria ambigua) and Murray Cod (Maccullochella peelii) (Percichthyidae) - Shams, Foyez; Dyer, Fiona; Thompson, Ross; Duncan, Richard P; Thiem, Jason D; Majtánová, Zuzana; Ezaz, Tariq (International journal of molecular sciences, 2019)
Karyotypic data from Australian native freshwater fishes are scarce, having been described from relatively few species. Golden perch (Macquaria ambigua) and Murray cod (Maccullochella peelii) are two large-bodied freshwater fish species native to Australia with significant indigenous, cultural, recreational and commercial value. The arid landscape over much of these fishes' range, coupled with the boom and bust hydrology of their habitat, means that these species have potential to provide useful evolutionary insights, such as karyotypes and sex chromosome evolution in vertebrates. Here we applied standard and molecular cytogenetic techniques to characterise karyotypes for golden perch and Murray cod. Both species have a diploid chromosome number 2n = 48 and a male heterogametic sex chromosome system (XX/XY). While the karyotype of golden perch is composed exclusively of acrocentric chromosomes, the karyotype of Murray cod consists of two submetacentric and 46 subtelocentric/acrocentric chromosomes. We have identified variable accumulation of repetitive sequences (AAT)10 and (CGG)10 along with diverse methylation patterns, especially on the sex chromosomes in both species. Our study provides a baseline for future cytogenetic analyses of other Australian freshwater fishes, especially species from the family Percichthyidae, to better understand their genome and sex chromosome evolution.
Keywords: karyotyp; florescence in situ hybridisation (FISH); zeměpis; sex determination; druhová specificita; Phylogeny; Sex Chromosomes; pohlavní chromozomy; Metaphase; telomery; comparative genomic hybridisation (CGH); Geography; Microsatellite Repeats; Female; karyogram; zvířata; pruhování chromozomů; DNA methylation; sladká voda; metafáze; Telomere; DNA Methylation; metylace DNA; ženské pohlaví; okounovití; Fresh Water; Karyotype; Male; fylogeneze; Chromosome Banding; Perches; Species Specificity; mikrosatelitní repetice; Animals; mužské pohlaví; Perciformes